Fecal occult blood versus DNA testing: indirect comparison in a colorectal cancer screening population - Brenner, Hermann; Chen, Hongda (Clinical epidemiology, 2017)
Fecal occult blood versus DNA testing: indirect comparison in a colorectal cancer screening population Hermann Brenner,1–3 Hongda Chen1,4 1Division of Clinical Epidemiology and Aging Research, German Cancer Research Center (DKFZ), 2Division of Preventive Oncology, German Cancer Research Center (DKFZ) and National Center for Tumor Diseases (NCT), 3German Cancer Consortium (DKTK), German Cancer Research Center (DKFZ), Heidelberg, Germany; 4Program Office for Cancer Screening in Urban China, National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Chaoyang District, Beijing, People’s Republic of China Background: A multitarget stool DNA test (MSDT) that showed higher sensitivity but lower specificity than a fecal immunochemical test (FIT) for hemoglobin in one recent study from the US and Canada, is increasingly used for colorectal cancer (CRC) screening, despite its ~20-fold higher costs compared to FITs. We aimed to assess diagnostic performance of a quantitative FIT in an independent study among participants of screening colonoscopy and to compare it with the previously reported performance of MSDT.Methods: A total of 3494 participants, aged 50–84 years, who underwent screening colonoscopy in private gastroenterological practices in Germany, and who provided a stool sample before colonoscopy to be evaluated by a commercially available quantitative FIT ( FOB Gold®) were included. Diagnostic performance (sensitivity, specificity) for detecting CRC or advanced precancerous lesions (APCLs) was evaluated by comparison of test results with findings at screening colonoscopy. In addition to the original cutoff, we used an adjusted cutoff yielding the same specificity as reported for the MSDT to enhance comparability.Results: The most advanced finding at colonoscopy was CRC and APCL in 30 (0.86%) and 359 (10.3%) cases, respectively. At a cutoff yielding the same specificity as reported for MSDT (86.6%), the sensitivities (95% CI) of the FIT for detecting CRC and APCL >1 cm were 96.7% (82.8–99.9%) and 54.3% (48.3–60.3%), respectively. These sensitivities are higher than those reported for MSDT (92.3% and 43.6%, p=0.66 and 0.003, respectively).Conclusion: In this large screening population, FIT showed equivalent or better diagnostic performance in comparison to reported performance of MSDT. Keywords: colorectal cancer screening, fecal occult blood test, fecal immunochemical test, sensitivity, specificity, test performance
Gesehen am 18.07.2017